2015
DOI: 10.3390/ijms160818270
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenines and Multiple Sclerosis: The Dialogue between the Immune System and the Central Nervous System

Abstract: Multiple sclerosis is an inflammatory disease of the central nervous system, in which axonal transection takes place in parallel with acute inflammation to various, individual extents. The importance of the kynurenine pathway in the physiological functions and pathological processes of the nervous system has been extensively investigated, but it has additionally been implicated as having a regulatory function in the immune system. Alterations in the kynurenine pathway have been described in both preclinical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 66 publications
1
51
0
3
Order By: Relevance
“…Recently, evidence has indicated that kynurenine dysregulation is most prominent during the acute phases of MS, whereas kynurenine metabolite levels in MS patients in remission are similar to those of controls [31]. In particular, inhibition of the first enzyme that converts tryptophan to kynurenine metabolite (indoleamine 2,3-dioxygenase) seems to be associated with the reduction of disease activity [32], evidence in line with our findings documenting an increase in tryptophan level during IFN ß treatment. Nevertheless, how IFN ß dynamically influences different levels of the kynurenine pathway has not been adequately explored.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, evidence has indicated that kynurenine dysregulation is most prominent during the acute phases of MS, whereas kynurenine metabolite levels in MS patients in remission are similar to those of controls [31]. In particular, inhibition of the first enzyme that converts tryptophan to kynurenine metabolite (indoleamine 2,3-dioxygenase) seems to be associated with the reduction of disease activity [32], evidence in line with our findings documenting an increase in tryptophan level during IFN ß treatment. Nevertheless, how IFN ß dynamically influences different levels of the kynurenine pathway has not been adequately explored.…”
Section: Discussionsupporting
confidence: 90%
“…These pathological changes were also observed in animal models, such as experimental autoimmune encephalomyelitis (EAE) (Rajda et al, 2015;Vogt et al, 2009). Currently, besides inhibition of inflammation, the promotion of nerve regeneration is a principle strategy for the treatment of MS (Cristofanilli et al, 2013).…”
mentioning
confidence: 96%
“…The neuroinflammatory process can be significantly decreased by inhibition of IDO-1 enzyme activity, considerably reducing disease exacerbation ( 119 ). Monaco et al revealed corresponding clinical evidence of depressed TRP levels in both serum and CSF of MS patients ( 69 ).…”
Section: Kp Influence On the Immune Systemmentioning
confidence: 99%